CYCLOPHOSPHAMIDE ALTERED THE MYOCARDIAL MARKER ENZYMES: PROTECTION PROVOKED BY HESPERIDIN IN RATS - Meenu shrivastava; Vasundra Kar; Shobhit Shrivastava (International Journal of Phytomedicine, 2013)
Our present experimentation was carried out to evaluate the efficacy of hesperidin (HDN) (100mg/kg body weight), administered orally for 7 days on cyclophosphamide (CP) elicited oxidative damage on rat heart. Cardiotoxicity inflicted by single intraperitoneal injection of CP (200mg/kg body weight) was manifested by exalted levels of CPK (creatinine phosphokinase),ALT (alanine transaminase), AST (aspartate transaminase) and LDH (lactate dehydrogenase).CP induced group depicted significant amelioration in level of MDA (malondialdehyde) , HDN treated group demonstrated inflated levels of above enzymes and decreased level of MDA. These levels were reversed to normal levels in HDN treated group. Thus result of our study is in concordance with the notion that HDN is adept in combating myocardial free radical damage provoked by CP thus proving its protective potential.